1995
DOI: 10.1002/jmv.1890460313
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus antibodies among patients with hemophilia, blood donors, and hepatitis patients

Abstract: The presence of antibodies to hepatitis E virus (HEV) was studied among hemophiliacs, blood donors, and hepatitis patients. Four of 296 (1.4%) hemophiliacs and 5 of 1,275 (0.4%) donors were confirmed as positive for HEV antibodies (difference was not significant: P = 0.07). Parenteral transmission of HEV to hemophiliacs was thus rare or nonexistent. Seven of 187 hepatitis patients were found with HEV antibodies (IgG and IgM). Six persons fell ill shortly after arriving from HEV-endemic countries. The seventh p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
8

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 8 publications
1
28
0
8
Order By: Relevance
“…In Brazil (a country where HEV is nonendemic), 2.6 to 3% of healthy blood donors were found to have HEV antibodies (10). Similarly, the presence of HEV antibodies was reported in countries where HEV is nonendemic in Europe, including Spain, Sweden, Germany, Greece, England, Finland, Italy, and The Netherlands (1,15,16,42,43). Similar data were observed in human populations in Ontario (M. Fearon [Ontario Ministry of Health, Toronto, Ontario], personal communication).…”
Section: Discussionmentioning
confidence: 86%
“…In Brazil (a country where HEV is nonendemic), 2.6 to 3% of healthy blood donors were found to have HEV antibodies (10). Similarly, the presence of HEV antibodies was reported in countries where HEV is nonendemic in Europe, including Spain, Sweden, Germany, Greece, England, Finland, Italy, and The Netherlands (1,15,16,42,43). Similar data were observed in human populations in Ontario (M. Fearon [Ontario Ministry of Health, Toronto, Ontario], personal communication).…”
Section: Discussionmentioning
confidence: 86%
“…They also suggested that the parenteral transmission of HEV may have occurred in Japanese patients with hemophilia via non-virus-inactivated coagulation factors (34). Other studies in different countries showed lower HEV seropositivity among hemophilia patients (45)(46)(47)(48) than Japan.…”
Section: Discussionmentioning
confidence: 99%
“…In der Regel war dabei unbekannt, ob die Infektion auf die Gabe von Blutprodukten zurückzuführen war oder auf anderem Weg erworben worden war. In der Literatur sind nur wenige Untersuchungen von Hämophiliepatienten berichtet worden [196,197]; in keiner dieser Untersuchungen gab es Hinweise auf ein erkennbares HEV-Infektionsrisiko durch Gerinnungspräparate. Allerdings wurde in einer japanischen Studie bei äl-teren Hämophiliepatienten, die auch mit nicht virusinaktivierten Gerinnungsprä-paraten behandelt worden waren, eine erhöhte Antikörperprävalenz festgestellt [198].…”
Section: Definition Von Ausschlusskriterienunclassified